"EMOTIVE VOCABULARY IN LINGUISTICS" - Maksudova Khurshida Abdurahimovna; Shakhnoza Bakhodirovna Ergasheva (Scientific Impulse, 2023)
Emotive vocabulary in linguistics refers to a set of words and phrases that carry emotional weight. These words do more than just convey information; they infuse our language with feelings and sentiments. In this essay, we'll explore how emotive vocabulary influences our communication and its diverse roles in different contexts.